2013
DOI: 10.1007/s00428-013-1440-2
|View full text |Cite
|
Sign up to set email alerts
|

One-step nucleic acid amplification (OSNA) for intraoperative evaluation of sentinel lymph node status in breast cancer: a comparative study between CK19 protein expression and CK19 mRNA level in primary tumors and lymph node metastasis

Abstract: The one-step nucleic acid amplification (OSNA) method is an increasingly used procedure for intraoperative analysis of sentinel lymph node (SLN) status in breast cancer patients. It measures cytokeratin19 (CK19) mRNA copy numbers in homogenized samples of SLN; CK19 has been chosen for identifying node metastasis because most breast cancers express this molecule. However, to avoid false-negative OSNA results, testing the preoperative needle core biopsy (NCB) of breast carcinomas for CK19 by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Touch imprint cytology (TIC), frozen section (FS) analysis and onestep nucleic-acid amplification (OSNA) represent the most common techniques available to intraoperatively detect breast cancer axillary sentinel lymph node (SLN) metastasis [8,9]. However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Touch imprint cytology (TIC), frozen section (FS) analysis and onestep nucleic-acid amplification (OSNA) represent the most common techniques available to intraoperatively detect breast cancer axillary sentinel lymph node (SLN) metastasis [8,9]. However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The most common ones include frozen section (FS), touch imprint cytology (TIC) [8] and one-step nucleicacid amplification (OSNA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The major cellular functions of cytokeratins are mechanical support, cytoarchitecture, cell migration, and signal modulation26. Among keratins, the KRT19 is the smallest member of the type I keratin family and is known as a tumor marker in several kinds of malignancies12131415161718. Regarding the function of KRT19 in cancers, the expression of KRT19 might contribute to the invasiveness of hepatocellular carcinoma (HCC)27.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of identifying novel partner receptor for TD mutant HER2, we found that cytokeratin 19 (KRT19) is bind to wild type HER2 in A549 lung cancer cell line. KRT19, which is a member of the keratin intermediate filament family of proteins, is well known to be generally overexpressed in various cancers121314151617, and its fragment known as CYFRA has been shown to be a tumor marker in some subsets of lung cancers1218. In this study, we determined the binding sites of KRT19 and HER2 and investigated the impact of KRT19 and HER2 interactions in signal transduction pathways to decode their possible roles in oncogenesis.…”
mentioning
confidence: 99%
“…This possibility was estimated to occur in 2–3% of breast cancer evaluated using immunohistochemistry. However, Pegolo et al (26) showed that cases with negative CK19 immunostaining had a significant CK19 expression at mRNA level. We have also adopted and recommend the use of intra-operative cytological smear before starting an OSNA procedure to avoid false-negative cases.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%